Proceedings of the 11th Koli Calling International Conference on Computing Education Research 2011
DOI: 10.1145/2094131.2094161
|View full text |Cite
|
Sign up to set email alerts
|

Experiences of prospective high school teachers using a programming teaching tool

Abstract: During their time at school few high school students are exposed to basic computing concepts as Computer Science (CS) is not considered to be an important part of the curriculum. As a result many high school students do not encounter programming during their studies. In the UK, despite newly qualified CS and ICT (Information and Communication Technology) teachers having specific subject knowledge, in recent years schools have steadily 'watered down' the content of CS courses and have aligned the subject with d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 6 publications
0
9
0
1
Order By: Relevance
“…In order to contribute to knowledge in this research area, some additional work based on these suggestions has been completed. Described in [20] a study involving 23 trainee High School ICT/Computer Science teachers, which reports on their experiences using a robot simulator to teach Java programming concepts, has been performed. It was found during this study how the implementation of a robot simulator was found to offer an enjoyable and effective method of teaching programming despite only moderately improving the trainee's confidence in their ability to teach programming.…”
Section: Discussion On the Results Of The Slrmentioning
confidence: 99%
“…In order to contribute to knowledge in this research area, some additional work based on these suggestions has been completed. Described in [20] a study involving 23 trainee High School ICT/Computer Science teachers, which reports on their experiences using a robot simulator to teach Java programming concepts, has been performed. It was found during this study how the implementation of a robot simulator was found to offer an enjoyable and effective method of teaching programming despite only moderately improving the trainee's confidence in their ability to teach programming.…”
Section: Discussion On the Results Of The Slrmentioning
confidence: 99%
“…Following the SR an early version of the Kebot robot simulator was used during exploratory empirical research to seek an initial insight using such a tool, to gain feedback and to help with the generation of ideas. Details of this work have been disseminated previously (Major et al, 2011). Whilst the research design of the exploratory studies was informal, several important findings were established.…”
Section: Motivationmentioning
confidence: 99%
“…Futschek e Moschitz [8] relata as suas experiências com o uso de estratégias de ensino de programação para crianças, que são baseadas em objetos tangíveis, as quais se mostraram capazes de diminuir a abstração para determinadas explicações e de estabelecer um ambiente motivador. Já Major et al [9] discorre sobre a sua experiência pedagógica através da utilização de uma ferramenta de ensino de programação baseada em um simulador de robôs.…”
Section: Scaico Et Alunclassified